If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 13 = 2x + 1 Reorder the terms: 13 + -1x = 2x + 1 Reorder the terms: 13 + -1x = 1 + 2x Solving 13 + -1x = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 13 + -1x + -2x = 1 + 2x + -2x Combine like terms: -1x + -2x = -3x 13 + -3x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 13 + -3x = 1 + 0 13 + -3x = 1 Add '-13' to each side of the equation. 13 + -13 + -3x = 1 + -13 Combine like terms: 13 + -13 = 0 0 + -3x = 1 + -13 -3x = 1 + -13 Combine like terms: 1 + -13 = -12 -3x = -12 Divide each side by '-3'. x = 4 Simplifying x = 4
| 2c+3=50c-6 | | 6-5c=-4c | | -2a+3=9 | | 3(0)-9(3)=15 | | 2n-5=4n-7 | | 48=4n-4 | | 8a+18=6a+30 | | 4x^2+378x-4248.5=0 | | 8k=1 | | z/3=19=25 | | 10z-6=14 | | sin(3x)+cos(6x)=1 | | 8a-18=6a+30 | | 3v-5=8 | | k/2-1=1 | | (11x)+(6x+5)=180 | | 2=3d-4 | | 4z-7=9 | | 5a-6=56 | | f(x)=2x^2+6x-1 | | 20=x+x*0.2 | | 6x=(8-0.25x)-(6-0.75) | | 7x+11=3*4+2 | | 100+20a=220 | | 5a+6= | | 2x+7*3=22*3+x | | 9(y+1)(y+1)-9=0 | | 4(y-1)(y-1)-9=0 | | .4*x+.6*8=9.5 | | 11g+3=12g | | -17-2a=1 | | -4+17(x)=183 |